Pengaruh Terapi Reiki terhadap Kecemasan pada Orang dengan HIV/AIDS (ODHA) - I Nengah Sumirta; AA Sri Sasmita Laksmi; I Wayan Candra; IGA Harini; IDM Ruspawan (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2020)
This study attempts to prove the influence of anxiety ODHA Reiki Therapy .Using research pre experimental design with the kind of research one-group pre-post test design .Data collection with simple random sampling , the large sample 16 .Measuring anxiety T-MAS use .Data analysis with Wilcoxon Test Range , show any impact Reiki Therapy to anxiety ODHA with p value 0,017 on 5% significance.